Seduce me with sapphires - Feather, Jane (Zebra historical romance., 2020)
A FLAWED CUT . . . The Honorable Miss Fenella Grantley has a secret: she<U+2019>s been taking drama classes and longs to be an actress. Ladies of her standing don<U+2019>t appear on stage, but Fenella has never been one for society<U+2019>s rules. She<U+2019>s quite excited to take on the challenge of reading the leading role in a new play<U+2014>until she meets the playwright. Toeing the line between infuriating and irresistible, his first impression leaves a lot to be desired . . . OR A RARE FIND? Edward Tremayne, illegitimate son of the Earl of Pendleton, scorned the ton years ago, making his own way in the world, and pursuing his literary gifts on the side. The only thing he misses from his old world is Fenella. Since seeing her at a ball when she was a young debutante, he<U+2019>s never forgotten her. Now that fate has reunited them, Edward<U+2019>s determined to make her his leading lady<U+2014>in every way. But the only thing they see eye to eye on is their intense passion for each other. And it just may take a massive misunderstanding for their love to get on the same precious page . . .